The Effect of Profit Sharing Financing on The Profitability of Islamic Banks in Indonesia - Laylan Syafina (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
The purpose of this study is to analyze the effect of mudharabah financing and musyarakah financing on the profitability of Islamic banks in Indonesia as proxied by ROA both partially and simultaneously. Research methodology with quantitative research where secondary data is used in the form of ROA data, Mudharabah Financing, and Musyarakah Financing using a time span from 2018 to 2020 using monthly data. Processing data using Eviews 10 application with classical assumption test and hypothesis testing. The results show that mudharabah financing has no effect on the profitability of Islamic banks. Musyarakah financing has a significant and significant impact on the profitability of Islamic banks. The simultaneous test shows that mudharabah financing and musyarakah financing have a significant effect on the profitability of Islamic banks.